Snowflake epitope matching correlates with child-specific antibodies during pregnancy and donor-specific antibodies after kidney transplantation - Niemann, Matthias; Strehler, Yara; Lachmann, Nils; Halleck, Fabian; Budde, Klemens; Hönger, Gideon; Schaub, Stefan; Matern, Benedict M.; Spierings, Eric (Frontiers in Immunology, 2022)
Development of immunizer-specific HLA antibodies (ISA) remains a major risk factor for graft loss following organ transplantation, where ISA are directed towards patches on the three-dimensional structure of the respective organ donor’s HLA proteins. Matching donors and recipients based on HLA epitopes appears beneficial for the avoidance of ISA. Defining surface epitopes however remains challenging and the concepts underlying their characterization are not fully understood. Based on our recently implemented computational deep learning pipeline to define HLA Class I protein-specific surface residues, we hypothesized a correlation between the number of HLA protein-specific solvent-accessible interlocus amino acid mismatches (arbitrarily called Snowflake) and the incidence of ISA. To validate our hypothesis, we considered two cohorts simultaneously. The kidney transplant cohort (KTC) considers 305 kidney-transplanted patients without ISA prior to transplantation. During the follow-up, HLA antibody screening was performed regularly to identify ISA. The pregnancy cohort (PC) considers 231 women without major sensitization events prior to pregnancy who gave live birth. Post-delivery serum was screened for ISA directed against the child’s inherited paternal haplotype. Based on the involved individuals’ HLA typings, the numbers of interlocus-mismatched antibody-verified eplets (AbvEPS), the T cell epitope PIRCHE-II model and Snowflake were calculated locus-specific (HLA-A, -B and -C), normalized and pooled. In both cohorts, Snowflake numbers were significantly elevated in recipients/mothers that developed ISA. Univariable regression revealed significant positive correlation between ISA and AbvEPS, PIRCHE-II and Snowflake. Snowflake numbers showed stronger correlation with numbers of AbvEPS compared to Snowflake numbers with PIRCHE-II. Our data shows correlation between Snowflake scores and the incidence of ISA after allo-immunization. Given both AbvEPS and Snowflake are B cell epitope models, their stronger correlation compared to PIRCHE-II and Snowflake appears plausible. Our data confirms that exploring solvent accessibility is a valuable approach for refining B cell epitope definitions.